If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (k + -5)(k + -4) = 0 Reorder the terms: (-5 + k)(k + -4) = 0 Reorder the terms: (-5 + k)(-4 + k) = 0 Multiply (-5 + k) * (-4 + k) (-5(-4 + k) + k(-4 + k)) = 0 ((-4 * -5 + k * -5) + k(-4 + k)) = 0 ((20 + -5k) + k(-4 + k)) = 0 (20 + -5k + (-4 * k + k * k)) = 0 (20 + -5k + (-4k + k2)) = 0 Combine like terms: -5k + -4k = -9k (20 + -9k + k2) = 0 Solving 20 + -9k + k2 = 0 Solving for variable 'k'. Factor a trinomial. (4 + -1k)(5 + -1k) = 0Subproblem 1
Set the factor '(4 + -1k)' equal to zero and attempt to solve: Simplifying 4 + -1k = 0 Solving 4 + -1k = 0 Move all terms containing k to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1k = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1k = 0 + -4 -1k = 0 + -4 Combine like terms: 0 + -4 = -4 -1k = -4 Divide each side by '-1'. k = 4 Simplifying k = 4Subproblem 2
Set the factor '(5 + -1k)' equal to zero and attempt to solve: Simplifying 5 + -1k = 0 Solving 5 + -1k = 0 Move all terms containing k to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1k = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1k = 0 + -5 -1k = 0 + -5 Combine like terms: 0 + -5 = -5 -1k = -5 Divide each side by '-1'. k = 5 Simplifying k = 5Solution
k = {4, 5}
| 4p-3=6p+5 | | 136=.5h(10+7) | | 46=2(2x+5)+2x | | X-5=2y | | -2t-7+3t-2=2 | | x-5+74=180 | | -6+x/4=-8 | | 7h=84 | | 4.7p-3.2=25 | | y=e^8x | | -5(3x+4)=55 | | 3(4+3)-2=12x+7 | | 120=4(6)(4)+2(4)h | | 8w^3=200w | | 1/1/3+1/2= | | 3(4x+6)=42 | | 3x+7-4x=-12 | | (m+2)(m^2+3m-6)+(m^2-2m+4)= | | z-2-z+1=z+1 | | 3x^3+8x^2=3x | | -2x=-2x+7 | | 1/15+1/2= | | 4x^3-19x^2=5x | | 90=x+(x-7) | | 36=x-2(x-2+x+4) | | 4(x^2+9x-10)=0 | | (x/3)-(5/6)=(1/2) | | 106+x+40=180 | | 3x=(1/5) | | 5-2x=-4x-7is | | 8(2+3)=72 | | 14-2w=18w |